FULFILLING THE RIGHT TO INFORMATION AND COMMUNICATION FOR DETAINEES AT THE SEMARANG IMMIGRATION DETENTION CENTER - Simandjuntak, Marcella Elwina; Saraswati, Rika; Wahyati, Endang; Sarwo, Budi; Rahman, Arief (Universitas Katolik Soegijapranata, 2025)
Detainees are those who are currently undergoing a detention process for violating Law Number 6 of 2011 concerning Immigration. They are in Indonesian territory without valid travel documents or residence permits, or their residence permits are no longer valid. This research aims to determine the fulfillment of communication and information rights services (for Detainee) during the pandemic and post-pandemic COVID-19 and the obstacles in implementing these services. The method used in the research is a qualitative method approach with an analytical descriptive. The data used are primary and secondary. Primary data was collected by conducting interviews with Rudenim Semarang officers. Secondary data was collected by conducting literature studies. The research results show that the right to information and communication for Detainees is provided both during the COVID-19 pandemic and post-COVID-19 Pandemic, which includes the right to information regarding the continuation of cases faced by Detainees given by forwarding information to Detainees regarding the extent to which Rudenim communicated with the Detainee's country of origin to return the Detainee to his country. The right to communication is exercised by providing a teleconference room that Detainees can use to contact colleagues or relatives via the Internet. The obstacle is the complaint from the Detainee about the time limitation during video calls and the extended response from the Detainee's country/government of origin.